2010
DOI: 10.3109/03009731003739851
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of general grief theory to Swedish women's experience after early miscarriage, with factor analysis of Bonanno's taxonomy, using the Perinatal Grief Scale

Abstract: BackgroundGrief is a normal phenomenon but showing great variation depending on cultural and personal features. Bonanno and Kaltman have nonetheless proposed five aspects of normal grief. The aim of this study was to investigate if women with miscarriage experience normal grief.Material and methodsContent analyses of 25 transcribed conversations with women 4 weeks after their early miscarriages were classified depending on the meaning-bearing units according to Bonanno and Kaltman's categories. In the factor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 29 publications
4
17
0
1
Order By: Relevance
“…A longitudinal study reported a significant proportion of patient’s psychological morbidity shortly after spontaneous abortion 4. The majority of women experience grief, depression or both after spontaneous abortion 5. Some women also experience anxiety, anger, posttraumatic stress, and guilt about future childbearing 6.…”
Section: Introductionmentioning
confidence: 99%
“…A longitudinal study reported a significant proportion of patient’s psychological morbidity shortly after spontaneous abortion 4. The majority of women experience grief, depression or both after spontaneous abortion 5. Some women also experience anxiety, anger, posttraumatic stress, and guilt about future childbearing 6.…”
Section: Introductionmentioning
confidence: 99%
“…All personnel must be knowledgeable of the symptoms of nonviable pregnancy to achieve this level of consistency. All responsible personnel should be educated in the normal grief reaction that patients experience following a miscarriage 8,9. Personnel in the health care chain now see a miscarriage as a significant event in the health and well-being of the patient 14,17…”
Section: Discussionmentioning
confidence: 99%
“…På senare år har forskningen runt upplevelsen av missfall kommit fram till att många kvinnor sörjer sitt blivande barn vid ett missfall, på samma sätt om de skulle sörja en avliden anhörig (3). Kvinnan undrar varför missfallet uppstod och kan skuldbelägga sig själv, eftersom det är hennes kropp som avbryter graviditeten (4).…”
Section: Teoretiskt Ramverkunclassified